Effects of metal components in PM2.5 derived from pig farm exposure on ovarian function and oocyte quality - Chae Yeon Kim; Geun Hye Park; Chae Rim Kim; Hyeonjin Kim; Ke Huang; Zhibin Liu; Nangwon Yee; Jiaxi Zhang; Doyoon Kim; Lei Ma; Eungyung Kim; Zae Young Ryoo; et al. (Journal of Hazardous Materials, 2026)

Genome-scale model-guided microbial engineering for valorization of agricultural waste biomass to poly(3-hydroxybutyrate) - Chae-Rim Jeong; Jaeseong Hwang; Young-Kwon Park; Jae Yong Ryu; Yong Hee Han; Ji Young Jeong; In Min Hwang; Ryeongeun Kim; Jung Eun Yang (Bioresource Technology, 2026)

Microbiome therapeutic PMC101 inhibits the translocation of carbapenem-resistant Klebsiella while enhancing eubiosis in antibiotic-induced dysbiosis mice - Hanieh Tajdozian; Hoonhee Seo; Sukyung Kim; Md Abdur Rahim; Hyun A. Park; Faezeh Sarafraz; Youjin Yoon; Hokyoung Kim; Indrajeet Barman; Chae-eun Park; Fatemeh Ghorbanian; Soyeon Lee; et al. (Medical Microbiology and Immunology, 2025)

Development of a Maritime Transport Emulator to Mitigate Data Loss from Shipborne IoT Sensors - Chae-Rim Park; Do-Myeong Park; Tae-Hoon Kim; Byung O Kang; Byung-Kwon Park (Journal of Marine Science and Engineering, 2025)
Recently, the maritime logistics industry has been transitioning to smart logistics by leveraging such technologies as AI and IoT. In particular, maritime big data plays a significant role in providing various services, including ship operation monitoring and greenhouse gas emissions assessment, and is considered essential for delivering maritime logistics services. Marine big data comprise real-world data collected during ship operations, but it is susceptible to loss due to temporal and environmental constraints. To address this issue, an Emulator is proposed to generate supplemental data, including location data, data count, and average distance, using accumulated maritime transport data. This study proposes an Emulator that repetitively generates new data such as location data, data count, and average distance using maritime transport data accumulated up to now. The location data is generated using the cumulative distance and trigonometric ratios based on the location information of standard routes. The data count and average distance are calculated based on user-input parameters such as voyage time and data interval. The generated data is inserted into a database and monitored on a map in real time. Experiments were conducted using maritime transport route data, and the results validated the effectiveness of the Emulator.

Purification of phenoloxidase from Haliotis discus hannai and its anti-inflammatory activity in vitro - Seung-Yub Song; Dae-Hun Park; Sung-Ho Lee; Han-Kyu Lim; Jin-Woo Park; Chae-Rim Jeong; Soo-Jung Kim; Seung-Sik Cho (Fish & Shellfish Immunology, 2023)

Integrated analysis of miRNA and mRNA expression profiles in diabetic mouse kidney treated to Korean Red Ginseng - Hye Rim Park; Seung Eun Lee; Yoojung Yi; Sangji Moon; Hyunkyung Yoon; Chae Won Kang; Jaetaek Kim; Yong Seek Park (Molecular & Cellular Toxicology, 2022)